Business law : legal environment, online commerce, business ethics, and international issues - Cheeseman, Henry R. (Upper Saddle River, N.J. : Pearson Prentice Hall, 2010)
For one or two semester undergraduate and graduate business law courses. Visually engaging, enticing and current examples with an overall focus on business. Business Law continues to be the most engaging text for students and professors by featuring a visually appealing format with enticing and current examples while maintaining its focus on business. Students will learn business law, ethics, and the legal environment in a way that will encourage them to ask questions and go beyond basic memorization. This edition of Business Law includes over 40 new cases, an up-to-date photo program, several new enticing discussion topics such as (3z(BEntrepreneurship: The Founding of Facebook(3y(B, (3z(BEthics: Animal Testing(3y(B, and Paul McCartney's Divorce, brief and easy-to-read chapters and cases, new on-line research activities, 25 new ABC news clips and a revised testbank with 500 new questions.s
Agency formation and termination -- Liabilities of principals, agents, and independent contractors -- Employment, worker protection, and immigration laws -- Labor law and collective bargaining -- Equal opportunity in employment -- Small businesses, entrepreneurs, and general partners -- Limited partnerships and limited liability limited partnerships -- Corporate formation and financing -- Corporate governance and the Sarbanes-Oxley Act -- Corporate acquisitions and multinational corporations -- Limited liability companies and limited liability partnerships -- Franchises and special forms of business -- Investor protection and online securities transactions -- Ethics and social responsibility of business -- Administrative law and regulatory agencies -- Consumer protection and product safety -- Environmental protection and global warming -- Antitrust laws and unfair trade practices -- Personal property and bailment -- Real property -- Landlord-tenant law and land use regulation -- Insurance -- Accountants' liability -- Wills, trusts, and elder law -- Family law -- International and world trade law
Includes bibliographical references and indexes.
1
Keywords: Business law -- United States